Heartwood Proportion and Physical-Mechanical Properties of Three Diameter Class of Gelam Wood (Melaleuca sp) from Central Kalimantan - Wahyu Supriyati; Tibertius A Prayitno; Soemardi Soemardi; Sri M Marsoem (Jurnal Ilmu dan Teknologi Kayu Tropis, 2014)
Gelam wood commonly use for house pole in peatswamp land of Central Kalimantan. However increasing the utilization of gelam wood lead to harvest a small diameter of trees. This research aims to study the percentage of heartwood, physical mechanical properties of gelam wood of different diameter class.Keyword: diameter class, gelam wood, heart wood, physical mechanical properties